Coat colours and mitochondrial lineages of ancient horses to document domestication - Cieslak, Michael (2012)
The domestication of the horse undoubtedly marks a major turning point in human history. In particular, the horse’s role in pack, draft, and riding led to profound changes in human societies. But nevertheless, very little is known about when, where, or how the earliest horse domestication happened. On account of the fact that molecular analyses on the basis of modern DNA had failed so far in shedding more light on the origin of horse domestication, in this dissertation the decision was made to use DNA from ancient horse remains (samples ranged from Alaska/northeast Siberia to the Iberian Peninsula and cover a temporal window from the Late Pleistocene period to the Middle Ages). On the basis of a coat colour phenotype analysis in this study, the conclusion was made that horse domestication started in the Eurasian steppe region around at least 3000 BC. In contrast to this clear outcome, mitochondrial lineages seem to be inappropriate for discovering a precise place of horse domestication within the Eurasian steppe. This was most likely due to the fact that there was a huge mitochondrial DNA diversity and a lack of a mitochondrial-genetic structure in the predomestic- and the earlydomestic horse population. Nevertheless, analyses of mitochondrial and coat colour data revealed that the Iberian Peninsula was not a horse domestication centre. Finally, this dissertation includes extensive review about the coat colour in domestic animals with regard to their wild ancestors. The two-fold goal of this review is to deepen the understanding of genetic backgrounds of coat colour traits on the basis of the current state of knowledge, as well as to contribute to a better comprehension of why it is more crucial to categorize coat colour traits on the basis of their molecular background than on any phenotypic classification. Die Domestikation des Pferdes markiert ohne Zweifel einen bedeutenden Wendepunkt in der Geschichte der Menschheit. Insbesondere die Rolle des Pferdes im Transport, als Zug- und Reittier, führte zu ...